1996
DOI: 10.2135/cropsci1996.0011183x003600060001x
|View full text |Cite
|
Sign up to set email alerts
|

Leaching and Mass Balance of 15N‐Labeled Urea Applied to a Kentucky Bluegrass Turf

Abstract: The fate of urea applied to Kentucky bluegrass (Poa pratensis L.) turf was studied over a 2-yr period using a combination of intact monolith lysimeters and small plots. Soil type was a Marlette fine sandy loam (fine-loamy, mixed mesic Glossoboric Hapludalfs). Urea was applied at a rate of 196 kg N ha-~ yr-~ in five equal applications of 39.2 kg N ha-i, using two application schedules. Treatments were fertilized at approximately 38-d intervals with the "Spring" treatment fertilized from late April through late … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

28
99
3

Year Published

2006
2006
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(130 citation statements)
references
References 0 publications
28
99
3
Order By: Relevance
“…Also, our percolate concentration results are similar to those presented by Geron et al (1993) for the fi rst year after seeding of Kentucky bluegrass for a comparable N application rate. In general, though, our percolate NO 3 -N concentrations are notably higher than other fi eld studies, which reported mean concentrations up to 4.6 mg L −1 for up to 244 kg N ha −1 yr −1 applied (Morton et al, 1988;Geron et al, 1993;Miltner et al, 1996;Guillard and Kopp, 2004;Mangiafi co and Guillard, 2006a). Because our fl ow-weighted average for percolate NO 3 -N concentration was greater than 3 mg NO 3 -N L −1 for our 0 N application treatment, our percolate NO 3 -N concentration results may be elevated relative to some studies due to differences in N mineralization potential of the soil.…”
Section: Percolate Nitrate Concentration and Masscontrasting
confidence: 87%
“…Also, our percolate concentration results are similar to those presented by Geron et al (1993) for the fi rst year after seeding of Kentucky bluegrass for a comparable N application rate. In general, though, our percolate NO 3 -N concentrations are notably higher than other fi eld studies, which reported mean concentrations up to 4.6 mg L −1 for up to 244 kg N ha −1 yr −1 applied (Morton et al, 1988;Geron et al, 1993;Miltner et al, 1996;Guillard and Kopp, 2004;Mangiafi co and Guillard, 2006a). Because our fl ow-weighted average for percolate NO 3 -N concentration was greater than 3 mg NO 3 -N L −1 for our 0 N application treatment, our percolate NO 3 -N concentration results may be elevated relative to some studies due to differences in N mineralization potential of the soil.…”
Section: Percolate Nitrate Concentration and Masscontrasting
confidence: 87%
“…These results are consistent with N recovery data for turfgrasses from several studies (Bowman et al, 2002;Bowman et al, 2000;Liu et al, 1993) but are considerably higher than N recovery reported in a number of field studies (Frank et al, 2001a, b;Miltner et al 1996;Joo et al, 1991). This difference may be due to the age and maturity of the experimental turf systems.…”
Section: Nitrogen Absorptionsupporting
confidence: 90%
“…The results of our experiment suggest that thatch may serve as a medium-term sink for atmospheric N deposition before it is decomposed and incorporated into SOM or lost from the system. This notion is supported by past N mass-balance studies in turfgrass systems (Engelsjord et al 2004, Horgan et al 2002, Miltner et al 1996, which have shown thatch to be a significant sink for fertilizer N.…”
Section: Discussionmentioning
confidence: 75%